2003
DOI: 10.1016/s0002-9440(10)63569-9
|View full text |Cite
|
Sign up to set email alerts
|

A Golden Hamster Model for Human Acute Nipah Virus Infection

Abstract: A predominantly pig-to-human zoonotic infection caused by the novel Nipah virus emerged recently to cause severe morbidity and mortality in both animals and man. Human autopsy studies showed the pathogenesis to be related to systemic vasculitis that led to widespread thrombotic occlusion and microinfarction in most major organs especially in the central nervous system. There was also evidence of extravascular parenchymal infection, particularly near damaged vessels A recent outbreak of a novel paramyxovirus su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
239
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(251 citation statements)
references
References 19 publications
10
239
2
Order By: Relevance
“…Serological studies indicated that NiV occurred in dogs, cats, horses and goats in the outbreak areas of Malaysia but all were effectively dead-end hosts [84]. Apart from pigs, experimental infection has been produced in cats [64], golden hamsters [94] and squirrel monkeys (Saimiri sciureus) [62]. Experimental studies have shown that infected cats shed NiV through the nasopharynx and in urine during viremic phase and of 2 cats infected, one recovered from experimental NiV infection with a high neutralizing antibody titer within 21 days [64].…”
Section: The Host Rangementioning
confidence: 99%
“…Serological studies indicated that NiV occurred in dogs, cats, horses and goats in the outbreak areas of Malaysia but all were effectively dead-end hosts [84]. Apart from pigs, experimental infection has been produced in cats [64], golden hamsters [94] and squirrel monkeys (Saimiri sciureus) [62]. Experimental studies have shown that infected cats shed NiV through the nasopharynx and in urine during viremic phase and of 2 cats infected, one recovered from experimental NiV infection with a high neutralizing antibody titer within 21 days [64].…”
Section: The Host Rangementioning
confidence: 99%
“…Reported lesions from experimentally infected animals resemble the lethal disease observed in humans, increasing the information on pathogenesis and representing suitable models to develop new immunotherapeutic approaches using antiviral drug testing and vaccine development against acute NiV infection [55]. For example, golden hamsters develop systemic vasculitis, pulmonary disease, and encephalitis.…”
Section: Lesionsmentioning
confidence: 99%
“…Mice are not a suitable model of NiV disease. Swiss mice inoculated either by the intranasal or the intraperitoneal routes do not develop clinical signs, but NiV antibodies can be produced after repeated infection [55]. However, NiV can be lethal if administered intracranially into suckling mice [58].…”
Section: Lesionsmentioning
confidence: 99%
“…Recently, one group showed induction of neutralizing antibodies to Henipavirus using an Alphavirus based vaccine (Defang et al, 2010). However, the study has been performed in mice which are not sensitive to NiV infection (Wong et al, 2003), preventing them from testing the efficiency of the vaccination. Monoclonal antibodies against NiV glycoproteins were shown to protect 50% of infected hamsters even when treatments started 24 h post infection and antiNiV F monoclonal antibodies protected hamsters against Hendra virus infection as well (Guillaume et al, 2009).…”
Section: Vaccines and Treatmentsmentioning
confidence: 99%